Dietary Habits and Lifestyle During Coronavirus Pandemic Lockdown: Experience From Lebanon - Cheikh Ismail, Leila; Hashim, Mona; Mohamad, Maysm N.; Hassan, Hussein; Ajab, Abir; Stojanovska, Lily; Jarrar, Amjad H.; Hasan, Hayder; Abu Jamous, Dima O.; Saleh, Sheima T.; Al Daour, Rameez; Osaili, Tareq M.; et al. (Frontiers in Nutrition, 2021)
This study aimed to examine the impact of quarantine on eating habits and lifestyle behaviors among the Lebanese adult population. A cross-sectional study was conducted using an online questionnaire designed on Google Forms between 3 June - 28 June 2020. The survey questions were adapted from the Short Food Frequency Questionnaire, the International Physical Activity Questionnaire Short Form, and the second version of the Copenhagen Psychosocial Questionnaire. A total of 2507 adults completed the questionnaire. During the lockdown, 32.8% claimed weight gain, 44.7% did not eat fruits daily, 35.3% did not eat vegetables on daily basis, and 72.9% reported drinking less than eight cups of water per day. Moreover, there was a significant increase in the number of meals consumed per day, consumption of homemade meals, sedentary time, stress, and sleeping disturbances during the pandemic compared to before the pandemic (all p<0.001). However, there was a significant decrease in physical activity engagement, sleep quality, and energy level during the lockdown compared to before the pandemic (all p<0.001). The study highlights that the COVID-19 lockdown was associated with unfavorable changes in dietary habits and lifestyle behaviors in Lebanon. Sleep and mental health were also negatively impacted by the pandemic.